Breakdown of Autonomously Functioning Thyroid Nodule Accompanied by Acromegaly After Octreotide Treatment - Nomoto, Hiroshi; Kameda, Hiraku; Nakamura, Akinobu; Tsuchida, Kazuhisa; Nagai, So; Atsumi, Tatsuya; Miyoshi, Hideaki (Frontiers in Endocrinology, 2019)
Patients with acromegaly are at increased risk of developing certain tumors, including goiter and thyroid nodules, and occasionally autonomous thyroid nodules. A 53-year-old woman presented at our hospital with untreated acromegaly. She had typical physical features of acromegaly with pituitary adenoma, and thyrotoxicosis with thyroid-stimulating hormone suppression was also confirmed. Thyroid ultrasonography and scintigraphy showed an autonomously functioning thyroid nodule on her right lobe. Because her thyrotoxicosis was mild, she was initially treated with octreotide for acromegaly. However, 1 month after octreotide administration, she developed neck pain and fever with transient thyrotoxicosis. The blood flow around the nodule then decreased and the excess trapping of isotope detected by scintigraphy was reduced, followed by normalization of insulin-like growth factor-1 levels and thyroid function. This case suggests that octreotide may have unexpected effects on autonomous thyroid nodules. However, further studies are needed to determine the clinical course of autonomously functioning thyroid nodules, including thyroid function and tumor manifestations, during octreotide therapy.